The Evolution of Body Size in Terrestrial Tetrapods - Fernanda S. Caron; Marcio R. Pie (Evolutionary Biology, 2024)
Body size is a fundamental trait in evolutionary and ecological research, given that it varies allometrically with several relevant features, such as life-history and physiological traits. Although previous studies uncovered many intriguing patterns, finding general principles of body size evolution in vertebrates has been elusive. In this study, we take advantage of recent advances in phylogenetic comparative methods and the availability of large-scale datasets to explore body size evolution in terrestrial vertebrates. Ancestral character estimation and disparity-through-time plots showed considerable variation in body size evolution, both across lineages and over time. In addition, regardless of the corresponding taxon, posterior predictive simulation demonstrated several consistent ways in which body size evolution in those groups departed from constant-rate models, namely: (1) there was considerable rate heterogeneity within each taxon, (2) there was a positive relationship between body size and its rate of evolution (i.e., large-bodied animals evolved faster than small-bodied ones), and (3) faster evolutionary rates near the present. Finally, geographical mapping of body mass and evolutionary rates revealed some similarities across taxa, but no clear latitudinal trends. Overall, these results indicate that there may be general patterns in the body size evolution on large scales in terrestrial vertebrates, with some intriguing taxon-specific differences.